¿"Progymnasmata" en los "Rhetoricae artis progymnasmata" de Thomas Blebel? - Curbelo Tavío, María Elena (2018)
In 1552, humanist Thomas Blebel composed a treatise entitled "Rhetoricae artis Progymnasmata". His work is a rhetorical treatise modelled on other manuals of precepts and doesn’t include a separate section dealing with the progymnasmata. In this article, we examine each of the fourteen progymnasmatic exercises individually in order to highlight possible coincidences with Bebel’s work and determine whether it actually is a 'progymnasmasta' treatise or just another one among numerous rhetorical works which have been edited and published during the15th and 16th centuries.
Keywords: Blebel, Thomas, -- c. 1540-1596; Humanismo; Retórica